2022
DOI: 10.3390/nu14081617
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Obesity on Bone Turnover Markers and Fracture Risk in Postmenopausal Women

Abstract: Background and aims: The relationship between obesity and bone metabolism is controversial. In recent decades, the protective role of obesity in the development of osteoporosis is questioned. The aims of this study are the following: to evaluate the differences in bone turnover markers between postmenopausal women with and without obesity and to compare the risk of fracture at five years between these groups. Methods: An observational longitudinal prospective cohort study of postmenopausal women with obesity (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 22 publications
0
13
0
1
Order By: Relevance
“…Other research has revealed that even though rats appeared to show beneficial improvements in bone mineral density in response to the presence of excess body mass in an osteoporosis model, 15 Turcotte et al, 16 confirmed obesity does appear to induce apparent beneficial increases in the bone mineral density of overweight human subjects, along with an enhancement of their bone micro architecture and bone strength. On the other hand, Lopez-Gomez et al, 17 found postmenopausal women who were deemed obese tended to show lower levels of bone formation markers than those who were deemed to be of a healthy weight. In addition, other data indicate that bone quality in the obese case may not be sufficient to successfully avert a fragility fracture because other factors are involved.…”
Section: Resultsmentioning
confidence: 97%
“…Other research has revealed that even though rats appeared to show beneficial improvements in bone mineral density in response to the presence of excess body mass in an osteoporosis model, 15 Turcotte et al, 16 confirmed obesity does appear to induce apparent beneficial increases in the bone mineral density of overweight human subjects, along with an enhancement of their bone micro architecture and bone strength. On the other hand, Lopez-Gomez et al, 17 found postmenopausal women who were deemed obese tended to show lower levels of bone formation markers than those who were deemed to be of a healthy weight. In addition, other data indicate that bone quality in the obese case may not be sufficient to successfully avert a fragility fracture because other factors are involved.…”
Section: Resultsmentioning
confidence: 97%
“…T2DM is associated with poor trabecular microarchitecture and bone strength in obese men. The higher fracture risk can be attributed to the effect of obesity on bone turnover markers (6). In the present study, the patient was selected based on the absence of diabetes complications with normal parathyroid and renal functions.…”
Section: Discussionmentioning
confidence: 99%
“…Body weight and body mass index are thought to be strong predictors of osteoporotic fractures. There have been several studies on the relationship between body mass index and bone mineral density in women, but only a few on men so far (6). The preservation of the skeletal system is determined by calcium, which is one of the essential minerals involved in bone homeostasis and is linked to increased bone minerals (7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, it has been reported that a high weight and body mass index (BMI) are protective factors against the risk of fracture [ 32 , 33 ]. However, clinical and epidemiological studies have shown that obesity may be a risk factor for fragility fractures [ 34 , 35 ]. Our results showed that obese rats exposed to hypoxia had a more deteriorated bone structure than normoweight rats who were subject to hypoxia.…”
Section: Discussionmentioning
confidence: 99%